Poverty Reduction for Extremely Poor Households of Malang City by the Implementation of Program Keluarga Harapan - Haliim, Wimmy (Research and Development Agency Ministry of Home Affairs, 2016)
This research is based on the low access of poor families to basic education and health care in Malang City that have an impact on social welfare and poverty problem. To overcome these problems, Ministry of Social Affairs of the Republic of Indonesia through Malang City Government and Social Department of Malang City implements Program Keluarga Harapan (PKH) in the form of conditional cash transfers to the Extremely Poor Households (RTSM). The result showed that the implementation of PKH has been implemented properly and according to the procedure and the number of RTSM recipients of PKH from year to year has decreased. Nevertheless, this program implementation does not significantly impact the number of poor people in the city of Malang in general.